The Political Marketing Strategy of Mayor and Deputy Mayor of Malang City (A Phenomenological Study on the Success of Mohammad Anton and Sutiaji (Mas) in Winning the Mayor Office) - Erfan Arif, M (KnE Social Sciences, 2018)
The objectives of this study are to reveal the political marketing strategy carried out by the winning team of Moch. Anton – Sutiaji, Mayor – Deputy Mayor candidate of 2013, and to understand their form of campaign. This study uses qualitative method with phenomenological approach. The findings of the study show that the winning team of the aforementioned pair understand the political marketing environment well. By knowing the need of voter market (society), utilizing the internal force of supporting organization, using the support of big capital (fund), relying on the managerial skill of the candidate, making a huge social investment (generosity), and arranging campaign activities relevant to the need of voter market in the form of holding free religious trip and giving door prize as the stimulant, this pair formed an accurate strategy in winning the office in 2013. Keywords: political marketing strategy, environment, campaign form